CHARACTERISTICS OF ISLAMIC EDUCATION IN THE PERSPECTIVE OF THE QURAN AND AL-HADITS - Lukman Hakim (Edukasi Islami: Jurnal Pendidikan Islam, 2020)
Formulating the goals of Islamic education must be prioritized before formulating other educational elements. Concern about educational goals is more important than concerns about educational materials or methods because educational materials and methods can change from time to time, while educational goals do not change. It is always constant and does not change. From an Islamic perspective, the purpose of education must be in line with the goal of human creation, namely to serve oneself or worship al-Kholiq Subhanahu Wata'ala and carry out the duties of the caliphate. Worship in Islam reaches to touch all aspects of life. It is not only limited to the rituals (asy-sya'aa'ir), which we are familiar with in prayer, fasting, zakat, and hajj. However, it also includes all movements and all activities that can improve human life quality or prosper human beings. Concerning the relationship with the Rabb of humans, they are servants of Allah. Meanwhile, about the relationship with the universe (kaun), man is the caliph. Therefore, it can be said that human life's purpose is to fulfill servitude and devotion - in a broad sense - to Allah Ta'ala. At the same time, his role on earth is as caliph (leader) in this universe